PEMBERDAYAAN BURUH BATIK BAKARAN DI KABUPATEN PATI PROVINSI JAWA TENGAH - neni alyani; Eko Budi Santoso; Nuke R. Maulandani; Enjang Hidayat (Jurnal Ilmu Pemerintahan Widya Praja, 2020)
This paper describes the efforts to empower batik laborers in Bakaran village, Pati Regency, Central Java. This study uses a qualitative approach by conducting interview and observation. The results show that there are problems with the implementation and empowerment methods in the Bakaran village. Some factors hinder the empowerment process of batik laborers that need to be resolved by changing the existing strategies and empowerment models according to the problems that arise. Keywords: empowerment; small business; laborer; batik.